(3GdMdd GdHgjLI aj aJM GdHQjLI hSjQI Gdedc GdgGTej SjOj eMeO GHf YHOGddg GdaGWejs - (3eMeO Hf CHj GdbGSej Hf eMeO Hf eMeO Hf SdjeGf GdeQGcTj,J (B1190 (3g` s ((3eMeO Hf GdYHGS Hf eMeO GdYhfj Ke GdLOjOj s)
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdLhGO GdPj ef YdjfG HGdLgGO s
(3BNQgG (B:s
(3hGddg Ph GdaVd GdYXje , hgh MSHfG hfYe Gdhcjd Bejf hGdMeO ddg QH GdYGdejf s
(3Jcde ajg Ydi aJM eOjfI GdHQjLI GdeYQhaI GdBf HGdLOjOI HGdeZQH GdCbUi Ref GdSdWGf GdeXaQ eMeO Hf YHOGddg GdMSfj GdeJhaj SfI (B1204(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3Odjd eDQN GdeZQH (B- (3U (B54 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B153 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs